KARAKTERISTIK PENGERINGAN BIJI KENARI MENGGUNAKAN EXPERIMENTAL DRYER TIPE RAK - M. Kasim; L.Ch.E. Lengkey; D.P.M. Ludong (Universitas Sam Ratulangi, 2018)
ABSTRACT Walnut trees are forest plants and have not been widely cultivated. Walnuts are native to Indonesia which are widely grown in eastern Indonesia, such as North Sulawesi, Maluku and Seram Island. This plant has the potential of economics, chemicals that are rich in bioactive content and antioxidant content with one of its components, namely polyphenols, walnuts grow in North Sulawesi where the seeds are widely used as supplement for cakes such as halua walnuts, dodol kenari, klaper koek, and others.Â The results of the observation showed the temperature distribution in the plenum room, drying chamber, temperature of the material and the outside air temperature of the drying air temperature was around 60 OC there was a temperature fluctuation in the drying chamber. Moisture levels are inversely proportional to changes in time. The longer the drying, the smaller the water content of walnut seeds shows the pattern of decreasing water content in this experiment with 5 replications showing an exponential pattern. The drying time of walnut seeds using this dryer takes 10 hours to obtain the average water content of walnut seeds at the end of drying of 7.17% wet base. Drying rate of walnut seeds on drying time occurs the drying rate decreases with the estimation model of drying rate of time is y = 3.8532e-0.151x with correlation coefficient RÂ² = 0.899 The drying constant obtained in each replication varies depending on water content and drying rate. Drying rate of walnut seeds on the water content of walnut seeds has a model of y = 0.3738e11.315x RÂ² = 0.9722.